P263 ROLE OF VITAL SIGNS AND INDICES OF SHOCK DERIVED FROM THEM IN THE SUSPICION OF MASSIVE PULMONARY EMBOLISM IN ELDERLY: THE ER AS A WINDOW ON REAL LIFE. (18th May 2022) - Savioli, G; Brattoli, M; Fumoso, F; Lapia, F; Mugellini, A; Martignoni, A; Ceresa, I; Muzzi, A; Novelli, V; Preda, L; Lava, M; Manzoni, F; et al.
Abstract: Purpose: Assess which vital parameters or shock parameters, in the real life of an Emergency Department, correlate with the presence of massive pulmonary embolism to see which ones can be of help to early suspect it. Methods: Single–center retrospective observational study, on all geriatric patients (> 75 y) who entered our ED, where they were diagnosed with acute PE. Enrollment began in 2016 and ended in 2019. We collected data from medical history, physical examination, laboratory tests, imaging; we calculated the characteristic scores from the diagnostic / therapeutic algorithm, both for the risk of PE (Wells, Geneva and Anni), and for the presentation of the risk of mortality at 30 days (sPESI). We then had all chest CTs retested by an experienced radiologist. We assess the correlation of vital parameters and shock indexes with the presence of massive pulmonary embolism. We took into consideration: the shock index (SI), the modified shock index (MSI) and the age–shock index (AGE_SI). Results: We enrolled 247 patients, with a mean age of 83 years and prevalence of female (F = 63%). Of these, 85 (34.4 %) presented with massive pulmonary embolism. There is no correlation between blood pressure, systolic and diastolic values, respiratory rate with the presence of massive pulmonary embolism (p > 0.05). However, there is a strong statistical correlation between heart rate values and the presence of massive pulmonary embolism (p < 0.0001). The shock index correlates with the presence of massive pulmonary embolism with good statistical strength (p < 0.001); the modified shock index correlates with the with even greater statistical strength (P = 0.0005). The age–shock index correlates with the presence of pulmonary embolism with excellent statistical strength (p < 0.0001). Conclusions: The study suggests that the alteration of shock indices, in particular of the AGE–shock index, correlate with the condition of massive pulmonary embolism. Taking into consideration these parameters, of very low cost, available from triage and obtainable in a few minutes at the medical examination, easily performed in the various Italian situations, can help to raise the suspicion of massive pulmonary embolism early and direct the patient more quickly towards the correct procedure therapeutic diagnostic.